Upodobitev travmatičnih dogodkov druge svetovne vojne v sodobnem češkem romanu - Šnytová, Jana (Jezik in slovstvo, 2022)
In contemporary Czech literature after 2000, there is a distinct tendency to create works that themat-ically originate from the period of the Second World War and depict in a non-ideological way the traumas caused by the problematic Czech-German coexistence. This is especially evident in the prose of middle-aged and younger female writers such as Alena Mornštajnová (1963), Hana Andronikova (1967–2011), Radka Denemarková (1968), Magdalena Platzová (1972), Jakuba Katalpa (1979) and Kateřina Tučková (1980). In the paper we discuss the novels of the mentioned authors with an em-phasis on the way they depic historical traumas from the Second World War in comparison with some contemporary Slovenian novels with the theme of the Second World War.
Keywords: 21. stoletje; 21st century; Andronikova, Hana; collective memory; collective trauma; Czech literature; Czech novel; češka književnost; češki roman; Denemarková, Radka; druga svetovna vojna; Katalpa, Jakuba; kolektivna travma; kolektivni spomin; Mornštajnová, Alena; Platzová, Magdalena; Second World War; Tučková, Kateřina